Collection building amongst heritage amateurs. Issue 3 (3rd July 2017) - Roued-Cunliffe, Henriette
Abstract : Purpose: The purpose of this paper is to gather an overview of different research fields that study collection building amongst heritage amateurs (e.g. amateur archaeologists, family and local historians, etc.). Design/methodology/approach: First, the paper will define the term heritage amateur and then identify possible fields in which these groups and their collection building have been studied. A snowball procedure was used to collect material for the study. Findings: While there is an overlap between some of the subjects and fields examined, there is a potential for more collaboration resulting in a deeper understanding of collection building amongst heritage amateurs. Research limitations/implications: The term heritage amateur is not widely used, and the identification and collection of material for the review rely on the definition and understanding of this term and the groups included under it. Practical implications: This review of existing literature will benefit researchers and practitioners in the fields of education, information science, museums, libraries and archival studies, as well as the multidisciplinary area of heritage studies. Social implications: There is a growing institutional and political interest in making digital heritage collections available to the general public, and this paper argues that an important part of this is understanding how heritage amateurs already do this. Originality/value: This paper will connect narrow interest areas such as participatory heritage or serious leisure and show how their angles on heritage amateurs differ and compare.